Comparison of the Martian thermospheric density and temperature from IUVS/MAVEN data and general circulation modeling. Issue 7 (14th April 2016) - Medvedev, Alexander S.; Nakagawa, Hiromu; Mockel, Chris; Yiğit, Erdal; Kuroda, Takeshi; Hartogh, Paul; Terada, Kaori; Terada, Naoki; Seki, Kanako; Schneider, Nicholas M.; Jain, Sonal K.; Evans, J. Scott; et al.
Abstract: Newly released Imaging Ultraviolet Spectrograph/Mars Atmosphere and Volatile EvolutioN (IUVS/MAVEN) measurements of CO2 density in the Martian thermosphere have been used for comparison with the predictions of the Max Planck Institute Martian General Circulation Model (MPI‐MGCM). The simulations reproduced (within one standard deviation) the available zonal mean density and derived temperature above 130 km. The MGCM replicated the observed dominant zonal wave number 3 nonmigrating tide and demonstrated that it represents a nonmoving imprint of the topography in the thermosphere. The comparison shows a great dependence of the simulated density and temperature to the prescribed solar flux, atomic oxygen abundances and gravity wave effects, with the former two being especially important in the thermosphere above 130 km and the latter playing a significant role both in the mesosphere and thermosphere. Key Points: Observed CO2 density and temperature agree well with model predictions Sensitivity of temperature and density on physical parameters is explored Longitudinal disturbances represent a stationary imprint of topography in the thermosphere